Precise modification of 2D materials by gas ion beams - Maguire, Pierce (Trinity College (Dublin, Ireland). School of Physics, 2017)
Precise modification of the geometry, stoichiometry and crystal structure of two dimensional (2D) materials will be instrumental in future nanodevice fabrication. Here, ion beams focused to a sub-nanometre scale have been demonstrated to modify the electrical and optical properties of graphene and molybdenum disulphide (MoS2)- Nanopores with sub-5 nm diameters were fabricated in graphene using a nitrogen gas-etching process moderated by an electron beam. A diffusion-based model was developed to quantify and illuminate the process. Defect-engineering was performed in graphene with a high level of precision by irradiation with He+ and Ne+. Separately the defect-engineering process was expanded for monolayer MoS2. Irradiation was also used to fabricate nanostructures with nanometre scale widths, to tune stoichiometry and to alter resistivity. Imaging using high resolution transmission electron microscopy demonstrated high quality He ion fabricated nanoribbons of ~7 nm and amorphous nanoribbons of ~1 nm. Finally, the effect of defects and heating parameters on the oxidation of M0S2 in air were explored, and the reaction was found to be substantially moderated through ion-induced defects.
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2017